1996
DOI: 10.1021/jp961156h
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Processes in Polycyclic Quinones:  The Light-Induced Antiviral Agent, Hypocrellin, and a Comparison with Hypericin

Abstract: Hypocrellin is a naturally occurring perylene quinone that possesses light-induced antiviral activity, most notably against the human immunodeficiency virus (HIV), as does the related molecule, hypericin. Whitelight continuum is employed to examine the excited-state processes in hypocrellin from the picosecond to the nanosecond time scales. These processes are assigned to intramolecular proton transfer, intersystem crossing, and interconversion between different conformations of hypocrellin, which is constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 37 publications
2
68
0
Order By: Relevance
“…For hypocrellin A, as observed in the fluorescence upconversion data and in the transient absorption data, 12,15 8 For hypocrellin A, the time constant of the longer-lived H atom transfer is very strongly dependent on viscosity. 14,17 (2) No deuterium isotope effect is observed for hypericin 7 or for the ∼10 ps component of hypocrellin A (Figure 5).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…For hypocrellin A, as observed in the fluorescence upconversion data and in the transient absorption data, 12,15 8 For hypocrellin A, the time constant of the longer-lived H atom transfer is very strongly dependent on viscosity. 14,17 (2) No deuterium isotope effect is observed for hypericin 7 or for the ∼10 ps component of hypocrellin A (Figure 5).…”
Section: Resultsmentioning
confidence: 81%
“…These have been the subject of several reviews [1][2][3][4][5] and have been referred to in detail in our previous work. One of the most interesting photophysical processes that these molecules execute is excited-state proton or H atom transfer, both intramolecular [6][7][8][9][10][11][12][13][14][15][16][17][18][19] and intermolecular. [20][21][22] We have suggested that the intermolecular proton transfer plays a role in certain aspects of the biological activity of hypericin and hypocrellin.…”
Section: Introductionmentioning
confidence: 99%
“…8,[25][26][27][28][29][30][31][32][33][34][35][36][37] By means of H/D substitution, investigation of methoxy analogues, and complementary studies using both transient absorption and fluorescence upconversion spectroscopies, we have argued that the major primary photophysical process in hypericin in organic solvents is excited-state intramolecular hydrogen-atom transfer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] We have argued that they also present a fascinating system with which to study excited-state intramolecular H-atom transfer. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Hypericin executes an intramolecular excited-state H-atom transfer in ∼10 ps. 20 This reaction is independent of solvent.…”
Section: Introductionmentioning
confidence: 99%